2021
DOI: 10.1136/bmjopen-2020-042749
|View full text |Cite
|
Sign up to set email alerts
|

Gendered economic, social and health effects of the COVID-19 pandemic and mitigation policies in Kenya: evidence from a prospective cohort survey in Nairobi informal settlements

Abstract: ObjectivesCOVID-19 may spread rapidly in densely populated urban informal settlements. Kenya swiftly implemented mitigation policies; we assess the economic, social and health-related harm disproportionately impacting women.DesignA prospective longitudinal cohort study with repeated mobile phone surveys in April, May and June 2020.Participants and setting2009 households across five informal settlements in Nairobi, sampled from two previously interviewed cohorts.Primary and secondary outcome measuresOutcomes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
108
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(126 citation statements)
references
References 36 publications
7
108
0
11
Order By: Relevance
“…Food insecurity was especially high for those households in which one or more people lost their income [34]. This was also found in Nairobi, where early in the pandemic 77% of women and 68% of men surveyed said they had skipped a meal due to COVID-19 in the previous week [35]. Other studies have found that adolescents who experience violence at home (especially those in low-income households), worsening relationships with adults in the household, and food insecurity are more likely to be depressed [11,36,37].…”
Section: Discussionmentioning
confidence: 79%
“…Food insecurity was especially high for those households in which one or more people lost their income [34]. This was also found in Nairobi, where early in the pandemic 77% of women and 68% of men surveyed said they had skipped a meal due to COVID-19 in the previous week [35]. Other studies have found that adolescents who experience violence at home (especially those in low-income households), worsening relationships with adults in the household, and food insecurity are more likely to be depressed [11,36,37].…”
Section: Discussionmentioning
confidence: 79%
“…Our quantitative and qualitative results suggest that poverty and loss of financial resources related to COVID-19 debilitated existing relationships and motivated transactional partnerships. Economic consequences of COVID-19 amplified a gender divide [27]. We found that existing relationships were destabilized and reevaluated in the face of a partner's income loss, leading to conflict, accusations of infidelity, and relationship dissolution.…”
Section: Discussionmentioning
confidence: 86%
“…Studies conducted during lockdowns in high-income settings demonstrate a sudden increase in shared time between cohabitating partners, with no impact on the overall quality of their relationships [16] or increases in conflict [25]. Studies centered on issues of intimacy during COVID-19 also report declines in the frequency of sexual intercourse among cohabitating partners during lockdown, related to increased anxiety and depression [24,26,27]. In our study, 28% of participants who spent more time with their partners described rising tensions and decreased emotional support, while 23% experienced the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…Robust data are essential for evaluating the hypotheses that lockdowns cause substantial harm or are futile and for targeting locations that are the most in need of resources. The impact of NPIs has been evaluated in various low-and middle-income countries, generating evidence of early reductions in income and food security and the rapid, substantial uptake of protective behaviors [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%